Intracellular vincristine levels in lymphoblasts affect treatment outcome in childhood B‐lymphoblastic leukaemia: Ma‐Spore ALL 2010 study. Issue 4 (23rd December 2020) - Jiang, Nan; Wang, Lingzhi; Xiang, Xiaoqiang; Li, Zhenhua; Chiew, Edwynn Kean Hui; Koo, Yok Moi; Lee, How Sung; Lin, Hai Peng; Tan, Ah Moy; Quah, Thuan Chong; Kham, Shirley Kow Yin; Goh, Boon Cher; et al.
Abstract : Aims: Vincristine (VCR) is a key drug in the successful multidrug chemotherapy for childhood acute lymphoblastic leukaemia (ALL). However, it remains unclear how VCR pharmacokinetics affects its antileukaemic efficacy. The objective of this study is to explore the VCR pharmacokinetic parameters and intracellular VCR levels in an up‐front window of Ma‐Spore ALL 2010 (MS2010) study. Methods: We randomised 429 children with newly diagnosed ALL to 15‐minute vs 3‐hour infusion for the first dose of VCR to study if prolonging the first dose of VCR infusion improved response. In a subgroup of 115 B‐ALL and 20 T‐ALL patients, we performed VCR plasma ( n = 135 patients) and intracellular ( n = 66 patients) pharmacokinetic studies. The correlations between pharmacokinetic parameters and intracellular VCR levels with early treatment response, final outcome and ABCB1 genotypes were analysed. Results: There was no significant difference between 15‐minute and 3‐hour infusion schedules in median Day 8 peripheral or bone marrow blast response. Plasma VCR pharmacokinetic parameters did not predict outcome. However, in B‐ALL, Day 33 minimal residual disease (MRD) negative patients and patients in continuous complete remission had significantly higher median intracellular VCR24h levels ( P = .03 and P = .04, respectively). The median VCR24h intracellular levels were similar among the common genetic subtypes of ALL ( P = .4). Patients homozygous for wild‐type ABCB1 2677GG had significantly higher median intracellular VCR24h ( P = .04) than 2677TT. Conclusion: We showed that in childhood B‐ALL, the intracellular VCR24h levels in lymphoblasts affected treatment outcomes. The intracellular VCR24h level was independent of leukaemia subtype but dependent on host ABCB1 G2677T genotype.